Public Documents Digitization: Towards Efficiency and Reduction of Municipal Expenses - María Maricely Chuquilin Condor; Segundo Amado Cajusol Yovera; Víctor Hugo Puican Rodríguez (F1000Research, 2026)
The digitization of documentation has become relevant in city halls as a means to maximize management and reduce costs in the context of fiscal austerity. In Latin America (and most particularly in Peru), local governments are still confronted with many structural problems, including procedural fragmentation, a very high reliance on paper-based documentation, and widely varying levels of technology-based solutions. In that sense, digitizing documents is not only about advancing technology but also uses revised information as organizational solutions that reduce the risk that municipalities face legally and operationally and promote more efficient use of limited municipal resources. This study followed a quantitative methodology based on a non-experimental cross-sectional design. The study took place in a city government in the Peruvian Amazon. The population consisted of 125 administrative staff; a sample of 95 respondents was considered representative. Information was obtained through a structured questionnaire and was subjected to descriptive statistics and inferential statistics—regression and analysis of variance—to analyse the relation between the digitization of documents and cutting of municipal costs. The findings indicate a significant positive relationship between documentary digitization and operating cost reduction, especially cost savings in terms of paper, physical storage, and administrative processing time. Yet the results suggest that the effect of digitization differs according to the dimension of quality. Legal risk and knowledge management-related components better explain cost reduction than simple technology adoption. Simultaneously, information security and auditing procedures were rated as moderately performing, implying a possible operational gap, which refines the financial gains of digitization. The results showed statistically significant relationships between certain aspects of document digitization and the perceived reduction in expenses in the municipality studied. Given the cross-cutting and inter-institutional nature of the research, the results should be interpreted as contextual evidence and not as conclusions that can be directly generalized to other municipalities or countries. The results indicate that financial benefits are less tied to a simple presence of digital tools and more to the organizational practices around using these tools. In terms of policy, the results are consistent with a phased, fiscally realistic digitization approach that emphasizes staff training, standardized digital processes, and basic legal risk controls in a limited budget municipality. The potential contribution of this research is that it presents context-specific evidence from a Peruvian municipality in the Amazonas region, which could be used by other similar local governments to extract practical lessons for achieving efficiency gains in the face of resource constraints.